Sensitivity to Pain Traumatization: A Higher-Order Factor Underlying Pain-Related Anxiety, Pain Catastrophizing and Anxiety Sensitivity among Patients Scheduled for Major Surgery - Valery Kleiman; Hance Clarke; Joel Katz (Pain Research and Management)
BACKGROUND: The present article addresses two related developments in the psychology of pain, and integrates them into a coherent framework to better understand the relationship between pain and trauma. The first is an emerging conceptualization regarding the nature of the hierarchical organization of major pain-related anxiety constructs. The second is the theoretical rationale and empirical evidence linking pain and symptoms of post-traumatic stress disorder.